Evaluation of the yield and baking quality of winter wheat (Triticum aestivum L.) varieties in different cropyears - Szabó, Éva (Acta Agraria Debreceniensis, 2013)
We have investigated the effect of the cropyear, the genotype, the nutrient supply and their interactions on the yield and the quality parameters of three different winter wheat genotypes in three different cropyears. The most disadvantageous influence on the yield averages was caused by the moist weather of 2010, when yield results fell behind the mean of the two other examined years and the nutrient optimum was around low doses. The optimal cropyear turned out to be the ordinary 2011, the best yield results were experienced during this cropyear. Although the drier periods in 2012 decreased the yield values, the varieties could realize high yield maximum values. Considering the yield results, Genius turned out to be the best variety. In respect of the quality traits, 2010 turned out to be the best cropyear in case of all the three varieties. Despite the dry weather of the spring of 2012, the precipitation fell during flowering and ripening phases had positive impact on the grain-filling processes and contributed to the development of better quality. As a consequence of the significantly lower amount of precipitation during the generative phenological phases, the worst quality parameters were realized by the varieties in 2011. In respect of crop year effect, 2010 was unfavourable for the amount of yield, but the most beneficial for the quality. 2011 was the most advantageous for the yield amounts but disadvantageous for the quality parameters. Although in 2012 extreme crop year effects were experienced after each other (dry and warm spring, moist and warm summer), the yield average and quality trait values were close to the yield averages of 2011 and quality parameters of 2010. Analyzing our results we can state that the average crop year was favourable rather for the yield. The appropriate amount of precipitation during the whole 2010 and that during the generative phenophases in 2012 favoured the development of good quality. Consequently, the appropriate amount of precipitation is essential for the development of good quality during the grain-filling period. The negative crop year effects were only compensated but not eliminated by the good nutrient supply. Genius achieved excellent yield averages but performed worse quality parameters than Mv Toldi, whose quality parameters were outstanding but the yield averages fell slightly behind those of Genius. Considering the yield results, the variety Genius turned out to be the best, while Mv Toldi was the best in quality.